Influence of Ion Diffusivity and Gas Solubility in Ionic Liquids on Li-Air Battery Performance. (30th August 2016) - Seo, Samuel; Song, Tangqiumei Maggie; Mizuno, Fuminori; Takechi, Kensuke; Brennecke, Joan F
Abstract : Owing to their extremely high theoretical energy density, non-aqueous Li-air batteries have received remarkable attention in recent years. Ionic Liquids (ILs), molten salts that are liquid at room temperature, have been investigated as potential electrolytes in Li-air batteries due to their negligible vapor pressure, good thermal stability, and wide electrochemical windows. However, compared to conventional organic electrolytes, ILs generally have higher viscosity and, consequently, lower ionic conductivity and ion diffusivity. Therefore, we have selected eight low-viscosity ILs containing the bis(trifluoromethanesulfonyl)imide ([TFSI] - ) anion, and their physical properties were characterized. The diffusivities of the cation and anion of the ILs were measured with pulsed-field-gradient spin-echo (PFG-SE) NMR Spectroscopy. In addition, the I-V performances of three characteristic ILs were tested in a Li-O2 battery. The solubility of O2 in the ILs and IL-Li[TFSI] mixtures, an additional property that can affect Li-air battery performance, was also measured using a gravimetric microbalance.